PEMBINAAN PEMANFAATAN E-COMMERCE DAN IMPLEMENTASI HOTSPOT - Sunarsan Sitohang; Anggiat Marubah Siringo (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2022)
The development of information technology is very rapid, one of which is the use of the internet for e-commerce and the use of hotspots. E-commerce has many benefits that are very likely to be realized currently. The implementation of community service activities for residents of Setengar village RT 05 RW 10 Tanjung Piayu by providing hotspot services as well as fostering the use of e-commerce and hotspot implementation aims to make residents have hotspot services and know and understand how to use e-commerce sites as a comparison reference. the price of an item or product. The specific target of the implementation of coaching in community service activities is that residents can take advantage of existing hotspot facilities to make online purchases from e-commerce sites, what are the steps for the shopping process and how to process transactions and what is needed when doing online shopping. The service team provides material and provides direct practice to coaching participants with the aim of all participants understanding the material presented by the service team. The process of implementing the activities will be carried out in several meetings by providing materials on the introduction of hotspots and how to install them and how to take advantage of hotspots and e-commerce. At each meeting the service team will evaluate and determine the sustainability of the coaching after the service activities that have been held for four meetings have been completed. The service team introduced the devices needed for hotspot installation, namely an access point router and provided installation training as well as introduced to residents some examples of the best and most trusted e-commerce sites, namely Bukalapak, Lazada, Tokopedia, OLX Indonesia, and elevenia.